Hybrid Learning as an Optional Language Learning Model in the Post Pandemic Era: A Systematic Literature Review - Dasuki Dasuki; Fadhilah Ramadhanty; Dewinta Mandalika; Muchlas Suseno (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
In the post-pandemic era, several technologies are recommended to address some of the issues faced by English language learning. The hybrid learning model comes to answer this challenge by utilizing technology through integrated online and offline learning in the classroom at the same time. Therefore, the paper aims to present a better understanding of hybrid learning in the English teaching and learning process during the post-pandemic era. The systematic searching method was applied, and 23 articles published from 2020 until 2023 were selected for this paper. Most of them were written in Asian nations. The finding shows that hybrid learning was well received by both teachers and students. Since this teaching model paved the way and provided a new window for English language practice, it has also been underlined by many academics and is being applied in English teaching and learning. In conclusion, the hybrid learning model can be an optional language learning model in the post-pandemic era.